Gating modulation of the KCNQ1 channel by KCNE proteins studied by voltage-clamp fluorometry - Nakajo, Koichi (Biophys Physicobiol, 2019)
The KCNQ1 channel is a voltage-dependent potassium channel and is ubiquitously expressed throughout the human body including the heart, lung, kidney, pancreas, intestine and inner ear. Gating properties of the KCNQ1 channel are modulated by KCNE auxiliary subunits. For example, the KCNQ1-KCNE1 channel produces a slowly-activating potassium current, while KCNE3 makes KCNQ1 a voltage-independent, constitutively open channel. Thus, physiological functions of KCNQ1 channels are greatly dependent on the type of KCNE protein that is co-expressed in that organ. It has long been debated how the similar single transmembrane KCNE proteins produce quite different gating behaviors. Recent applications of voltage-clamp fluorometry (VCF) for the KCNQ1 channel have shed light on this question. The VCF is a quite sensitive method to detect structural changes of membrane proteins and is especially suitable for tracking the voltage sensor domains of voltage-gated ion channels. In this short review, I will introduce how the VCF technique can be applied to detect structural changes and what have been revealed by the recent VCF applications to the gating modulation of KCNQ1 channels by KCNE proteins.